2020
DOI: 10.1177/0956797619882022
|View full text |Cite
|
Sign up to set email alerts
|

Probing Ovulatory-Cycle Shifts in Women’s Preferences for Men’s Behaviors

Abstract: The existence of ovulatory cycle shifts in women's mate preferences has been discussed controversially. There is evidence that naturally cycling women in their fertile phase, compared to their luteal phase, evaluate specific behavioral cues in men as more attractive for sexual relationships. However, recent research has cast doubt on these findings. We addressed this debate in a large, pre-registered within-subject study including salivary hormone measures and luteinizing hormone tests. One-hundred-fifty-seven… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 39 publications
1
17
1
Order By: Relevance
“…For these reasons, we do not think that our data and results, nor the results reported by Gangestad et al, are in favor of the ovulatory shift hypothesis. Indeed, the null results of our study are in line with other, recently published, large-scale replication studies investigating cycle shifts in preferences for masculine faces (Dixson et al, 2018;Jones et al, 2018;Marcinkowska et al, 2018a), bodies (Marcinkowska et al, 2018a;van Stein et al, 2019), voices (Jünger et al, 2018b) and behaviors (Stern, Gerlach, & Penke, 2019). Drawing null conclusions from just our data would be premature.…”
Section: The Problem Of Unfalsifiabilitysupporting
confidence: 86%
See 1 more Smart Citation
“…For these reasons, we do not think that our data and results, nor the results reported by Gangestad et al, are in favor of the ovulatory shift hypothesis. Indeed, the null results of our study are in line with other, recently published, large-scale replication studies investigating cycle shifts in preferences for masculine faces (Dixson et al, 2018;Jones et al, 2018;Marcinkowska et al, 2018a), bodies (Marcinkowska et al, 2018a;van Stein et al, 2019), voices (Jünger et al, 2018b) and behaviors (Stern, Gerlach, & Penke, 2019). Drawing null conclusions from just our data would be premature.…”
Section: The Problem Of Unfalsifiabilitysupporting
confidence: 86%
“…Importantly, many of the researchers of recently published studies investigating ovulatory cycle shifts (Dixson et al, 2018;Jones et al, 2018;Jünger et al, 2018a;Stern et al, 2019) opened their data, allowing for in-depth evaluations of the conducted analyses and the conclusions put forward, as shown in the current debate. However, all studies for which open data were provided reported no compelling evidence for the ovulatory shift hypothesis.…”
Section: Showcase For the Importance And Helpfulness Of Open Sciencementioning
confidence: 99%
“…However, nonreplications and methodological criticisms (Arslan et al, 2018;C. R. Harris et al, 2013;Jünger, Kordsmeyer, et al, 2018;Jünger, Motta-Mena, et al, 2018;Stern et al, 2020Stern et al, , 2021Stern & Penke, in press;Wood et al, 2014) have cast doubt on reports that hormonal changes across the cycle cause changes in partner preferences, as concluded by Gildersleeve et al (2014). Nevertheless, there is robust evidence that hormonal changes across the cycle lead to changes in sexual desire that do not occur in women using hormonal contraceptives (Arslan et al, 2018).…”
Section: Hormonal Contraceptive Use and Partner Preferencesmentioning
confidence: 99%
“…Nevertheless, there is robust evidence that hormonal changes across the cycle lead to changes in sexual desire that do not occur in women using hormonal contraceptives (Arslan et al, 2018). In addition, normally cycling women evaluate male bodies, voices, and behavior as generally more attractive in their fertile phase (Jünger, Kordsmeyer, et al, 2018;Jünger, Motta-Mena, et al, 2018;Stern et al, 2020Stern et al, , 2021.…”
Section: Hormonal Contraceptive Use and Partner Preferencesmentioning
confidence: 99%
“…Thomas et al [ 18 ] found that fertility status is unrelated to sociosexual attitudes and desires. Furthermore, contradictory findings regarding ovulatory shifts in mating preferences directing women’s attention and desire have been presented [ 15 , 19 , 20 , 21 ]. Nevertheless, researchers show evidence of multiple cues related to women’s fertility in reviews, see [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%